Stable isotope geochemistry of the Okenyenya igneous complex, Namibia : constraints on contamination and fluid interaction - Martinez, Iúma Aparecida (Department of Geological Sciences, 2016)
The δ¹⁸O values of coexisting silicate minerals in rocks comprising the tholeiitic olivine gabbro - quartz monzodiorite suite, are consistent with the attainment of isotope equilibrium and largely closed system conditions. The majority of the temperatures calculated by conventional mineral-pair thermometers are spurious, as a result of oxygen isotope diffusion during slow cooling. Closure temperatures for oxygen diffusion of 560ᵒC and 540ᵒC have been calculated for the anorthite-clinopyroxene and plagioclase-biotite mineral-pairs in the tholeiitic leucogabbro sample, respectively. The oxygen isotope data for the silicate minerals are consistent with contamination of the magmas by material having the oxygen isotope composition of the southern Etendeka rhyolite (δ¹⁸O = + 11.5‰). It is suggested that the assimilant may have been derived from the same source as the southern Etendeka rhyolite, as opposed to the rhyolite itself, which would be expected to occur at a high crustal level. Simple oxygen and strontium isotope mass balance calculations are used to constrain the lower (14 % and 19.5 % respectively) and upper (57 % and 71.6 % respectively) limits of the maximum possible amount of a southern Etendeka rhyolite contaminant assimilated.